2009
DOI: 10.1111/j.1748-0361.2009.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Rural‐Urban Continuum, Maternal Education and Adverse Birth Outcomes in Québec, Canada

Abstract: Differences in perinatal health exist across the rural-urban continuum, and maternal education has a modifying influence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 41 publications
1
26
1
1
Order By: Relevance
“…13 Most studies examining geographic barriers to maternity care in industrialized countries focused solely on perinatal death and infant mortality and morbidity, showing elevated rates among infants of women residing in rural areas. 14,[16][17][18][19][20] Geographic disparity in severe maternal morbidity has not been adequately examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Most studies examining geographic barriers to maternity care in industrialized countries focused solely on perinatal death and infant mortality and morbidity, showing elevated rates among infants of women residing in rural areas. 14,[16][17][18][19][20] Geographic disparity in severe maternal morbidity has not been adequately examined.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies of rural maternity care have focused solely on infant outcomes, [16][17][18][19][20]29,30 and population-based studies examining different components of severe maternal morbidity associated with rural residence in industrialized countries are rare. Our study showed that the risk of Note: CI = confidence interval, CNS = central nervous system, OR = odds ratio.…”
Section: Discussionmentioning
confidence: 99%
“…2e) could be due to the transmission of negative behaviours due to such behaviours being more common [50], and where less support for cessation may lead to smoking throughout pregnancy [51]. The dichotomized definition used to represent rural residential addresses may obscure mechanisms which can be modified by maternal factors such as education [52]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition to other pesticide exposures, proximity to agricultural activity is associated with coexposures to a variety of fertilizers that are applied in particularly large quantities in corn-growing areas (Ochoa-Acuña and Carbajo, 2009). Further, residence in agricultural areas has been linked to adverse birth outcomes with a wide range of postulated causes, which (in addition to fertilizers and pesticides) include microbial toxins (Missmer et al, 2006; Gelineau-van Waes et al, 2009), diet and lifestyle (Giordano et al, 2008; Elliott et al, 2009), and socioeconomic problems (Auger et al, 2009), although in many studies the specific risk factors remained unknown (Batra et al, 2007; Gonzalez et al, 2008; Messer et al, 2010). …”
Section: Discussionmentioning
confidence: 99%